Avaliação do leito cultivado com Zantedeschia aethiopica, de fluxo vertical ascendente, como pós-tratamento de reator anaeróbio de fluxo ascendente visando a remoção de matéria orgânica - Contim, Adriana (2009)
Anaerobic technology is a nowadays trend for treatment of wastewater, however, it requires post-treatment of the effluent to complement removal of organic matter and nutrients. The objective of this work was to assess the treatment efficiency of constructed wetland or cultivated bed (BC) with the macrophyte Zantedeschia aethiopica, with vertical upward flow on a bench scale as post-treatment of the up flow anaerobic reactor – UASB for removal of organic matter. A non-vegetated bed, with the same dimensions and characteristics of the wetland was used as control. Research was developed in two distinct stages. In the first, the support medium for UASB and the beds was expanded clay and also a superficial layer of coconut fiber. At this stage the system was operated in batches with a cycle time of 48 hours and fed with water from the Ribeirão dos Müller, located in Curitiba-PR. Results indicate that removal of organic matter had an average efficiency of 40.45 ± 22.17% for UASB, 9.42 ± 14.20% for the LC and 28.89 ± 23.20% for the control bed. The low efficiency of the system and some operational problems led to modifications that comprised the second stage. The system was then operated in continuous flow with a hydraulic retention time of 20 hours in the UASB and 24 hours in the beds and fed with synthetic wastewater. The support medium of the beds was changed to layers of expanded clay, crushed stone n° 1, gravel and medium sand. The BC then presented mean efficiency values for removal of organic matter of 59.46 ± 22.14 for gross COD and 56.95 ± 28.66 % for filtered COD. These values of efficiency are higher than those found in the control bed indicating the interference of plants in the posttreatment system. During the entire research, beds presented a rather unstable behavior regarding concentration of total suspended solids. Mean values of pH found in the treatment system are above 8.0 to generation of alkalinity in the system and buffering of the medium. Negligible concentrations of hydrogen sulfide dissolved in the liquid were found in the entire treatment system. UASB presented the highest mean concentration value of sulfate, disclosing the possibility of hydrogen sulfide generation. In the BC, reactions of sulfate reduction took place in the lower layers and thereby the sulfide produced was oxidized by oxygen supplied by the plants, reducing effluent odor. Overall mean efficiency found for the system UASB + BC was 82.68 ± 11.84% for gross COD and 80.83 ± 15.87% for filtered COD, meeting some standards for effluent disposal into bodies of water. Although the BC enhances post-treatment efficiency, the plants did not show satisfactory development. This was attributed to the low incidence of sunlight on the laboratory and also because plants remained partially submerged in the liquid.